Relações familiares retratadas em telenovelas brasileiras de grande audiência: aspectos relevantes e polêmicos em transformação - Souza, Cínthia Ferreira de (2010)
The soap opera is a cultural phenomenon of recognized importance in the Brazilian society and it’s arousing the interest of investigators once they reflect concrete social processes that don’t seem strange to the spectators reality. Many themes have already been approached in the soap operas characterizing a big context from the daily ordinary events till controversial situations, of rupture that force the debate. The investigation that was accomplished intended to identify and analyze how the family arrangements, the familiar and conjugal every day, the conflict situations and controversial occurrences are portrayed in cultural terms in six soap operas plots exhibited between 2003 and 2008 about 9 p.m. by Rede Globo of the TV. The data were collected from the synopses exam of the soap operas chapters and they were organized and discussed from the classic technique of analysis of the content. The way the Brazilian family is showed in the serial fiction of TV incorporates new family arrangements that the possibilities of relationships construction are producing in the last decades. The soap operas brought to the public discussion some subjects less explored or only explored by the society specific segments and they did it with characteristics that contest the stiffness of the traditions. In the plots predominate non prejudiced approaches in relation to the different themes considered in the investigation.